Training of female health workers (FHWs) to enhance the advocacy and communication skills on COVID-19 vaccine and routine Immunization in District Peshawar Khyber Pakhtunkhwa (KP) Pakistan in 2023—a report from the field - Al-Gunaid, Magid; Hussain, Zakir; Daoud, Leen; Akram, Khurram (Frontiers in Global Women's Health, 2025)
IntroductionIn 2021, a comprehensive evaluation was conducted across five countries, including Pakistan, to explore the factors influencing the demand for COVID-19 vaccines among priority groups. The study uncovered significant challenges, including low vaccination rates among females, limited trust in the COVID-19 vaccine, accessibility issues, and a notable gap in dose administration.MethodsTo address these challenges, a targeted pilot intervention was proposed in Peshawar, Pakistan. This intervention aimed to enhance vaccine demand among young women (aged 18–24), including pregnant and lactating women (PLWs), by equipping approximately 300 female health workers (FHWs) with improved advocacy and communication skills. These skills were designed to combat vaccine hesitancy and increase vaccine acceptance among women. Moreover, efforts were made to strengthen social support from community leaders. The pilot initiative encompassed baseline and endline evaluations to assess its impact. The baseline evaluation involved analyzing existing vaccination data, disaggregated by age and gender. Key informant interviews (KIIs) were conducted to capture qualitative insights into the perceptions of vaccines within the target population.FindingsData from the Department of Health KP and Expanded Program on Immunization Management Information System (EPIMIS) highlighted improvements in both COVID-19 and routine Expanded Program on Immunization (EPI) vaccinations across 25 union councils (UCs) in district Peshawar. KIIs with stakeholders, including health workers and community influencers, revealed enhanced knowledge and willingness to vaccinate, particularly among PLWs and females aged 18–24. The evaluation also observed increased confidence and reduced vaccine hesitancy due to advocacy sessions. Additionally, training of FHWs significantly improved their knowledge and attitudes towards COVID-19 vaccination and routine EPI, contributing to the overall success of the intervention. Monitoring visits further validated the effective conduct of advocacy sessions by trained health workers, leading to increased vaccination uptake in the community.ConclusionThe comprehensive approach undertaken in this pilot intervention aimed not only to improve vaccine uptake but also to bolster confidence in the COVID-19 vaccine within the community. The findings and outcomes of this initiative provided valuable insights for future public health strategies, particularly in addressing vaccine hesitancy and increasing vaccine acceptance among priority groups.